Effect of Phenolic Compounds on Human Health - Gonzalez-Burgos, Elena; Gómez-Serranillos Cuadrado, M. Pilar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Phenolic compounds are non-essential dietary compounds that are found in many vegetables (i.e. onion, cabbage, broccoli and parsley), fruits (i.e. cherries, grapes, berries and pears), cereals and beverages (i.e. red wine, tea and chocolate). These heterogeneous compounds are produced as secondary metabolites. Structurally, these compounds are characterized by comprising an aromatic ring with one or more hydroxyl groups that can be classified into two groups: flavonoids and non-flavonoids. Phenolic compounds have received considerable attention for its health-promoting properties in many chronic disorders including diabetes, cardiovascular diseases, cancer and neurodegenerative diseases, among others. These health benefits are mainly attributed to its antioxidant properties. Phenolic compounds act as antioxidant by scavenging free radicals, metal chelation and endogenous antioxidant system upregulation (enzymatic antioxidants such as catalase, superoxide dismutase and glutathione peroxidase and non-enzymatic antioxidants such as glutathione).The consumption of exogenous medicinal plants and food rich in phenolic compounds represent a promising therapeutically to prevent many chronic diseases and improve health.This Special Issue entitled "Effect of Phenolic Compounds on Human Health" include research articles and review articles on phenolic compounds and its role in health (i.e. flavonoids and diabetes, polyphenols and liver diseases, polyphenols and obesity, polyphenols and cardiovascular diseases and polyphenols and neuroprotection).